Combined Criminal Acts in Islamic Criminal Law - Nurlilapratiwi; Abd. Alwi pase; Prawira Putra Amanda Siagian; Sahdia Tanjung (ISNU Nine-Star Multidisciplinary Journal, 2024)
Combined criminal acts in Islamic law, several criminal acts can be committed simultaneously. This study aims to analyze the punishment system for perpetrators who commit more than one crime, both according to Islamic law and the Criminal Code. In Islamic law there are theories of al-tadakhul (mutual entry) and al-jabbu (absorption), while the Criminal Code regulates combined criminal acts through several theories such as the Absorption System and Cumulation System. This study also aims to describe how the criminal punishment system for a double crime is carried out both according to Islamic law and the Criminal Code, and to provide a deeper explanation of the theory of combined criminal acts in Islamic law and the Criminal Code. Combined criminal acts are also one of the phenomena in criminal law that involve more than one criminal act committed by a perpetrator. In the perspective of Islamic criminal law, combined criminal acts in Islamic criminal law and how the application of punishment is in accordance with sharia principles. Through a normative approach by examining primary sources such as the Qur'an, hadith, and works of classical scholars, this study is that criminal law in Islam has a unique mechanism in responding to a combination of criminal acts, including by considering the type of violation, the purpose of preventing crime, and justice for victims. The results of the study indicate that Islamic law prioritizes restorative justice and prevention as the main basis for sentencing for criminal acts, by considering the objectives of sharia. This study has implications for a deeper understanding of the flexibility and relevance of Islamic criminal law in handling complex cases in the contemporary era.